Pharmacogenomic profile of a central European urban random population-Czech population - Proietti Riccardo; Maranho Neto Geraldo A.; Kunzova Sarka; Re Oriana L.; Ahola-Olli Ari; Heliste Juho; Gonzalez-Rivas Juan P.; Vinciguerra Manlio (Public Library of Science, 2025)
The genetic basis of variability in drug response is at the core of pharmacogenomics (PGx) studies, aiming at reducing adverse drug reaction (ADR), which have interethnic variability. This study used the Kardiovize Brno 2030 random urban Czech sample population to analyze polymorphisms in a wide spectrum of genes coding for liver enzymes involved in drug metabolism. We aimed at correlating real life drug consumption with pharmacogenomic profile, and at comparing these data with the SUPER-Finland Finnish PGx database. A total of 250 individuals representative of the Kardiovize Brno 2030 cohort were included in an observational study. Blood DNA was extracted and 59 single nucleotide polymorphisms within 13 genes (BCHE, CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP3A5, F2, F5, IFNL3, SLCO1B1, TPMT, UGT1A1, VKORC1), associated to different drug metabolizing rates, were characterized by genotyping using a genome wide commercial array. Widely used drugs such as anti-coagulant warfarin and lipid lowering agent atorvastatin were associated to an alarmingly high percentage of users with intermediate/poor metabolism for them. Significant differences in the frequency of normal/intermediate/poor/ultrarapid/rapid metabolizers were observed for CYPD26 (p<0.001), CYP2C19 (p<0.001) and UGT1A1 (p<0.001) between the Czech and the Finnish study populations. Our study demonstrated that administration of some popular drugs to a Czech random sample population is associated with different drug metabolizing rates and therefore exposing to risk for ADRs. We also highlight interethnic differentiation of some common pharmacogenetics variants between Central (Czech) and North European (Finnish) population studies, suggesting the utility of PGx-informed prescription based on variant genotyping.